Gender and Digital Engagement in Panchkhal Municipality, Kavre, Nepal - Rawal, Sunil (Tribhuvan University Journal, 2024)
Correction: On 16th July 2024, the title of this article was changed from "Gender and Digital Engagement in Dhulikel Nepal" TO "Gender and Digital Engagement in Panchkhal Municipality, Kavre, Nepal". The purpose of this research is to delve into the detailed performance between the gender and digital participation in Panchkhal Municipality, which is located in the developing tech realm of Kavre District. The research investigates the subtle relationship between gender and digital dimensions, including self-rated digital literacy, internet habits, online safety mindfulness, and the desire to improve digital prowess. This research uses a combination of methods to access data from a field survey conducted within Panchkhal Municipality. This survey includes a wide range of participants, recording their gender preferences and digital behaviors. It also used quantitative analysis, primarily the Pearson Chi-Square test, to identify significant connections between gender and the examined digital factors. This method provides empirical support for a more nuanced sociological perspective on gender’s role in forming digital interactions. The findings reveal intriguing patterns: gender has no influence on self-rated digital competence levels, but it does have a significant influence on internet use patterns, online safety awareness, and the desire to improve one’s skills. These differences reveal gendered sections within tech engagement, implying that genders share inclinations while also having distinct choices, susceptibilities, and aspirations. Beyond the numbers, our research emphasizes the importance of fostering all-encompassing digital literacy initiatives that take gender differences into account. Furthermore, we advocate for just technological ecosystems while acknowledging the complex dance of norms in society, gender personas, and tech behavior. This study adds to our sociological understanding of how gender presents on the digital canvas by unraveling gender- infused threads interwoven into digital interaction. These insights transcend academia, guiding us to craft actions and policies that shape a more equitable, inclusive digital future in Panchkhal Municipality, Kavre Palanchowk district and beyond.